Bacterial strains isolated from sinusitis infections and their drug resistance profiles in Nasiriyah (Iraq) - A. W. Malik; S. M. Mohsen; A. K. Mohsen; S. Q. Mohammad; O. A. Mohsein (Regulatory Mechanisms in Biosystems, 2025)
Sinusitis, which is also referred to as rhinosinusitis, is one of the most prevalent causes of clinical visits in the United States. It is also one of the primary reasons why antibiotics are prescribed. This study aimed to i dentify the types of bacteria that cause sinusitis and find out the most effective types of antibiotics to optimise the success of treatment . Samples we re collected with a sterile swab , which was gently inserted into the nasal cavity, then directed towards the sinus area. They were grown on nutrient media such as b lood agar, MacConkey agar and Mueller-Hinton agar. Gram stain technology was used to identify bacteria such as Staphylococcus sp. , Streptococcus sp. , Haemophilus influenzae , Moraxella catarrhalis , biochemical tests were carried out, including catalase, oxidase, carbohydrate fermentation, and API ( analytical profile in dex) test strips were used . The sensitivity of bacteria to antibiotics was examined using CLSI standards to ensure the accuracy of the results by culturing the bacteria on Mueller Hinton agar medium and placing the antibiotic disk s . T he results were recorded for sensitivity, intermediate sensitivity and resistance . Z one diameter measurement s were taken to determine the effectiveness of the antibiotic s . The results showed that the percentage of positive cases for H. influenzae was 36.7%, Moraxella catarrhalis 24.7%, S. aureus 16.0%, S. pneum o niae 15.3%, and Staphylococcus epidermidis 8.0%. H. influenzae showed full sensitivity to ceftriaxone, gentam y cin, and va n comycin, while Moraxella catarrhalis was fully sensitive to ceftriaxone, imipenem, vancomycin, and oxacillin. S. aureus was sensitive to ceftriaxone, imipenem, gentam y cin, vancomycin, and erythromycin. S. pneumoniae showed sensitivity to penicillin, gentam y cin, and vancomycin. S. epidermidis was sensitive to gentam y cin, nitrofurantoin, and erythromycin. The study co n cluded that the bacteria H. influenzae and Moraxella catarrhalis were the most common in sinusitis, with high sensitivity to common antibiotics such as ceftriaxone and gentam y cin. This indicates the effectiveness of these antibiotics in treatment, which helps guide appropriate treatment and reduce bacterial resistance.